Peran Komunikasi SBAR Dalam Pelaksanaan Handover Di Ruang Rawat Inap RSPS - Umi Hidajah; hanna harnida (NERSMID : Jurnal Keperawatan dan Kebidanan, 2018)
Information communication is common in the world of health care. One of the forms of information communication activity is the handover activity or the official report or hand over. Every day, before the nursing activity in one shift begins with the activity. Hand over is a communication process activity between 2 shift nurses to provide information relating to patients and facilitate the continuation of the patient care process. Hand over activities are activities that have been handed down in the world of nursing, but the standard, effectiveness and skills of hand over communication has never been given formally at the level of nursing education. So that new nurses learn about hand over through these activities are carried out every day and from experienced nurses. The design used in this research is descriptive research. This research was conducted in September 2017 at RSPS Surabaya. The population used in the study were nurses in two inpatient wards with a total sample of 40 nurses. Data collection tool used in this research is questionnaire. Analysis of data used is univariate analysis used is calculate proportion of communication SBAR. The results showed that in the situation communication component (S) mostly in the effective category, the communication component of background (B), assessment (A) and recommendation (R) mostly in 87% the effective category. In general, most of the nurse communication in the category effective, so it is expected for the hospital can improve the effective communication so that can improve the quality of nursing service, conducting communication training and giving effective communication module so that patient can feel satisfaction in service in hospital.